2020
DOI: 10.21134/rpcna.2020.mon.2035
|View full text |Cite
|
Sign up to set email alerts
|

Ajuste familiar durante la pandemia de la COVID-19: un estudio de díadas

Abstract: La pandemia mundial del COVID-19 ha traído una gran cantidad de cambios vitales para la sociedad. Ante esta situación, las familias y sus hijos han tenido que adaptarse a nuevas rutinas y situaciones, lo que puede haber aumentado o agravado el padecimiento de sintomatología emocional. No obstante, la presencia de resiliencia y de estrategias de regulación emocional positivas, puede amortiguar este impacto en las familias con hijos pequeños. El objetivo del presente trabajo es conocer las variables que explicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
0
6
0
11
Order By: Relevance
“…The demands of parent-adolescent dynamics have increased during the COVID-19 pandemic, as parents struggle to balance their work while supporting their children’s autonomy and educational and mental health needs (von Soest et al, 2022 ; Wang et al, 2022 ). In the COVID-19 context, adolescents are at a lower risk of contagion than older populations (Lacomba-Trejo et al, 2020 ), but are at a higher risk of lower well-being and higher distress due to the interruption of their developmental tasks (Orellana & Orellana, 2020 ). Adolescents thus require more support from their primary caregivers, who are most often their mothers (Lacomba-Trejo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The demands of parent-adolescent dynamics have increased during the COVID-19 pandemic, as parents struggle to balance their work while supporting their children’s autonomy and educational and mental health needs (von Soest et al, 2022 ; Wang et al, 2022 ). In the COVID-19 context, adolescents are at a lower risk of contagion than older populations (Lacomba-Trejo et al, 2020 ), but are at a higher risk of lower well-being and higher distress due to the interruption of their developmental tasks (Orellana & Orellana, 2020 ). Adolescents thus require more support from their primary caregivers, who are most often their mothers (Lacomba-Trejo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the COVID-19 context, adolescents are at a lower risk of contagion than older populations (Lacomba-Trejo et al, 2020 ), but are at a higher risk of lower well-being and higher distress due to the interruption of their developmental tasks (Orellana & Orellana, 2020 ). Adolescents thus require more support from their primary caregivers, who are most often their mothers (Lacomba-Trejo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mothers of children and teenagers had to pay attention to online classes and to keep an eye on the schoolwork of their children, while a more balanced distribution of the household chores was observed in those homes with no underage children [ 15 ]. According to Lacomba-Trejo et al [ 17 ] and their study carried out in Spain in families with underage children, it was observed that the children who were confined at home due to the COVID-19 lockdown measure showed deficient strategies for emotional regulation, which generated an adverse family climate and caused emotional exhaustion in their mothers.…”
Section: Introductionmentioning
confidence: 99%
“…La Revista Latinoamericana de Estudios de Familia, en esta oportunidad comparte investigaciones que transitan por la comprensión de los cambios y transformaciones en las familias latinoamericanas en un contexto de transición, algunos de ellos presentados en el seminario internacional. Los dos primeros, destacan el desafío de cuidar la salud mental de la población en general, puesto que, en el contexto de la crisis sanitaria, esta ha aumentado y agravado notablemente el padecimiento de sintomatología emocional en forma de estrés, ansiedad o depresión en la niñez, juventud y adultez (Lacomba-Trejo et al, 2020). Son múltiples los esfuerzos para que la mayoría de la población se adapte y construya una vida cotidiana posterior a una crisis sanitaria.…”
unclassified